Television Newscasting Analysis: Towards Establishing Language Rules in Writing News Script in Filipino for Broadcast Media - Santos-Bulaong, M (KnE Social Sciences, 2018)
This study pertained to the grammatical errors in primetime newscasting of the two biggest network in the country, TV Patrol of ABS-CBN and 24 Oras of GMA-7. This aimed to correct the errors that were documented, believing that the one of the most popular media, Television Newscasting, will aid in teaching and enriching the Filipino Language because of its wide access and influence making teaching and learning process natural and with less burden. The researcher viewed the errors positively and progressively. Corder’s (1971) error analysis was used to construct the descriptive taxonomy from the news stories/narratives of TV Patrol for the month of October and 24 Oras for August. For data gathering, the initial procedure was monitoring and documenting of news. The news for one month was transcribed and was kept in a data repository called data bank. Language manuals and guides were the basis in classifying the errors. The errors were analyzed and were classified into word Addition, Omission, Correct Usage, Proper Word, and Proper Word Order Category. And to ensure the accuracy of the results, the researcher used triangulation method through Personal Analysis, Focus Group Discussion and Final Discussion attended by experts in the Filipino Language and practitioners in newscasting, and from this, Filipino language rules, which can be the basis of news script writing for Broadcasting, were created. Keywords: Television newscasting, news script, descriptive taxonomy, error analysis, language rules in Filipino,